Neuroticism and Forgiveness as Predictors of Dating Violence among Student Victims of Toxic Relationships - Astrid Juen Latuputty; Arthur Huwae (Kuras Institute, 2026)
Dating violence is a serious issue among university students in romantic relationships, especially for those with a history of toxic relationships. It can negatively impact psychological well-being. Key psychological factors, such as neuroticism and forgiveness, influence this condition. Given the importance of healthy romantic relationships in emerging adulthood, this study examined how neuroticism and forgiveness predict dating violence in university students with toxic relationship experiences. This study used a quantitative approach with multiple linear regression. The sample included 404 Indonesian university students aged 18–25, all with toxic relationship experiences. Participants were selected with incidental sampling and online questionnaires. The study used the Neuroticism Scale (α = 0.898), Forgiveness Scale (α = 0.749), and Dating Violence Scale (α = 0.955). Data were analyzed using Jamovi version 2.7.6. The results showed that neuroticism and forgiveness simultaneously had a significant effect on dating violence (F = 513.5; p < 0.001). Partially, neuroticism was found to be a significant positive predictor of dating violence, while forgiveness was a significant negative predictor of dating violence. This study highlights that neuroticism acts as a risk factor, whereas forgiveness serves as a protective factor against dating violence among university students with a history of toxic relationships. Therefore, it is essential to develop psychological interventions that focus on emotional regulation and the enhancement of forgiveness to promote healthier romantic relationships.